THE ROLE OF CAPITAL ADEQUACY IN MEDIATING THE EFFECT OF GREEN FINANCING ON THE FINANCIAL PERFORMANCE OF ISLAMIC BANKING: PATH ANALYSIS APPROACH - Cici Widya Prasetyandari; Zahida I’Tisoma Billah; Yeni Kartikawati; Norhayati (FORPIM PTKIS ZONA TAPAL KUDA, 2026)
Green financing is financing that supports sustainable development. The Financial Services Authority (OJK) is a state institution that supports sustainable finance, this is reinforced by regulations that encourage financial institutions to contribute to environmentally friendly activities. One of the financial institutions that implement green financing is Islamic banking. Banks are not only required to improve environmental sustainability, but also improve financial performance. This study aims to determine the role of capital adequacy in mediating the influence of Green Financing on the financial performance of Islamic banking in Indonesia. The population in this study is all Islamic commercial banks registered in the FSA, while the sample is determined through purposive sampling method. The data analysis method used is path analysis. The results showed that Green financing has a significant effect on financial performance. Capital adequacy has no significant effect on financial performance. Green financing has no significant effect on capital adequacy. Thus, it can be concluded that capital adequacy does not act as a mediation of the influence of green financing on the financial performance of Islamic banks in Indonesia.